2006
DOI: 10.1111/j.1365-2885.2006.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of levamisole in broiler breeder chickens

Abstract: The pharmacokinetics of levamisole was studied in 20 broiler breeder chickens (chickens that give eggs to breed broilers). A single dose of levamisole (40 mg/kg) was administered orally or intravenously to chickens before the onset of egg production, prelay (age = 22 weeks), and repeated at the peak of egg production (age = 32 weeks). A high-pressure liquid chromatographic with ultraviolet detection method (HPLC-UV) was used for quantification of levamisole in plasma. Using compartmental analysis, levamisole f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
0
9
0
2
Order By: Relevance
“…No local or systemic adverse effect was observed following IV, IM, and SC administrations of levamisole at a dose of 10 mg/kg in red-eared slider turtles. Levamisole had no adverse effect at a dose of 40 mg/kg in chickens (El-Kholy et al, 2006) and at a dose of 5-10 mg/kg in ewes (Galtier, Escoula, Camguilhem, & Alvinerie, 1981). However, adverse effects, such as short-term (3-10 min) hyperexcitability, tremors, and deep respiratory movements, were observed following IV and IM administrations at a dose of 7.5 mg/kg in goats (Galtier et al, 1981;Sahagún et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No local or systemic adverse effect was observed following IV, IM, and SC administrations of levamisole at a dose of 10 mg/kg in red-eared slider turtles. Levamisole had no adverse effect at a dose of 40 mg/kg in chickens (El-Kholy et al, 2006) and at a dose of 5-10 mg/kg in ewes (Galtier, Escoula, Camguilhem, & Alvinerie, 1981). However, adverse effects, such as short-term (3-10 min) hyperexcitability, tremors, and deep respiratory movements, were observed following IV and IM administrations at a dose of 7.5 mg/kg in goats (Galtier et al, 1981;Sahagún et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The mean t 1/2 ʎz , V dss, and Cl T after IV administration of levamisole in red‐eared slider turtles were 5.0 hr, 0.81 L/kg, and 0.14 L hr −1 kg −1 , respectively. The mean t 1/2 ʎz , V dss, and Cl T of levamisole ranged from 0.96 to 2.34 hr, 2.14–13.6 L/kg, and 2.36–4.24 L hr −1 kg −1 in some mammalian and avian species, respectively (El‐Kholy et al., ; Fernández et al., ; García, Diez, Sierra, & Terán, ; Sahagún et al., ; Villanueva et al., ). These values indicate that levamisole has long t 1/2 ʎz , low V dss, and slow Cl T in red‐eared slider turtles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and 5.44 h (oral) (Fernández et al ., ); for goats t 1/2β = 1.44 h (oral) (Sahagún et al ., ); for swine, 9.3 and 6.9 h after oral and i.m. administration, respectively (Galtier et al ., ); for chicken, 5.7 h (El‐Kholy et al ., ); and for human; between 4.26 and 6 h (Luyckx et al ., ; Koussi et al ., ; Reid et al ., ). On the other hand, for rabbits, t 1/2β recorded were 1.42 h (Villanueva et al ., ) and 0.97 h (García et al ., ).…”
Section: Plasma Concentration Of Levamisole In Speckled Surubim Pseudmentioning
confidence: 99%
“…Since Berenshtein (21) first reported the potential effects of Se on animal humoral immunity, numerous investigations have demonstrated that Se plus vaccines increased immune system activation in poultry (22,23). In addition, LMS as an adjuvant was also confirmed to increase the antibody titer in chickens (24). In this study, we found that at all of the analyzed time points, serum IgG levels in chickens injected with the vaccine reconstituted with the combined solution of APS + Se + LMS were significantly higher than those in the control group.…”
Section: Discussionmentioning
confidence: 97%